Effect of Previous Cardiovascular Diseases on Long-Term Outcomes of Acute Myocardial Infarction: Data of the Outpatient Registry "PROFILE-IM" - N. P. Kutishenko; D. P. Sichinava; E. P. Kalaydzhyan; V. A. Evdakov; E. A. Kasparova; S. Yu. Martsevich (Столичная издательская компания, 2018)
Aim. Within the framework of the outpatient registry of patients with acute myocardial infarction (AMI), to assess the influence of factors in medical history, especially cardiovascular diseases (CVD) preceding AMI, on the long-term results of the underlying disease.Material and methods. 160 patients who  sought medical care to the outpatient clinic from March  01,  2014 to June 30,  2015 after  AMI were included into the registry. Patients were observed for at least 1 year (maximum 2.5 years). The primary end point (PEP) of the study were death from any cause,  recurrent cardiovascular complications (non-fatal AMI, cerebral stroke), and urgent hospitalization due to the worsening of the current CVD.Results. After 1 year of follow-up, 9 (6%) patients died (8 from CVD). A recurrent myocardial infarction occurred in 8 patients, and cerebral stroke in 1 patient. 20 patients were hospitalized due to CVD exacerbation. In total PEP was registered in a fifth part of patients (36 people). Factors that had a negative impact on the endpoint were age (relative risk [RR] 1,05; 95% confidence interval [CI] 1.01-1.09, p=0.016), the presence of cardiovascular diseases or conditions reflecting the severity of the underlying disease before the reference event: ischemic heart disease (RR 2.37; 95%CI 1.05-5.34, p=0.038), previously AMI (RR=5.93; 95%CI 2.28-15.4, p<0.001), percutaneous coronary intervention (RR 9.84; 95%CI 2.02-48.06, p<0.005), disability (RR 4.37; 95%CI 1.82-10.46, p<0.001).Conclusion. The long-term life and  disease prognosis in patients with AMI remains quite severe.  Adverse long-term outcomes of the  disease are largely determined by anamnestic factors, primarily the  presence of ischemic heart  disease before  the  reference event,  previous AMI. The study indirectly demonstrated that percutaneous coronary intervention in patients with stable ischemic heart disease, at least, does not improve the prognosis of the disease.